Performance of NiMo-Al2O3 catalyst in biokerosene production via hydrocracking of dirty palm oil. Issue 1 (31st December 2022) - Buchori, Luqman; Widayat, W.; Muraza, Oki; Prasetyaningrum, Aji; Prameswari, Jedy; Widiyadi, Aditya; Guspiani, Gema Adil
Abstract : Energy consumption in the transportation sector steadily rises each year, requiring an effective solution to meet the demands present. In this study, biokerosene was produced through the hydrocracking process using NiMo-Al2 O3 as a catalyst and dirty palm oil as raw material. The synthesised catalyst was characterised by scanning electron microscopy (SEM) and X-ray diffraction (XRD), while the biofuel product which was analysed by gas chromatography-mass spectrometry (GCMS). The results showed that in the hydrocracking process, the decarboxylation and decarbonylation reactions were the dominant pathways. The conversion of biokerosene increased with increasing catalyst concentration, temperature and reaction time. The highest biokerosene yield was found to be 56.38% with a catalyst concentration of 0.01 g-catalyst/g-oil, 3 h reaction time and 450°C reaction temperature. The optimum catalyst concentration was 0.04 g-catalyst/g-oil, while the optimum temperature was 550°C and the optimum reaction time was 3 h.